Revisiting trauma and redemption through death drive among female suicide bombers in selected novels - Abdullah, Amalia Qistina Castaneda (2019)
There has been a surge of research conducted within trauma studies. Nevertheless, due to the scarcity of literary works written on female suicide bombers, a new genre of trauma amongst women, this field of trauma needs further research. This is to give more attention to an important reality: how Muslim women are becoming active participants in a violent world of terrorism. This research focused on fictional characters who became suicide bombers. Through textual analysis these selected novels on female suicide bombers written by the likes of Anne Speckhard’s Bride of ISIS (2015), Yasmina Khadra’s The Attack (2007), Thomas Lee Howell’s Martyr (2015), and Gabriella Ambrosio’s Before We Say Goodbye (2010), are analysed to gain insight into the belief system of Muslim female suicide bombers, where they regain meaning that is higher than the biological self which was in the past traumatised. My critique then is on the system or ideology that preys on the vulnerability of these women which successfully recruits them and inculcate a belief system born out of a desire for assertion of life, identity and agency. An ideology that promises them redemption that is mutual and reciprocated, which makes the formation of a suicide bomber easier. Utilising the concept of trauma’s engraving memory and history by Cathy Caruth and Lacan’s death drive theory, this thesis seeks to have a better understanding of the realisation that suffering is an instrument that could exploit someone who is traumatised in order to victimise others. These novels are narratives of how female suicide bombers are created from an existence ruled by fear, guilt, and pain, seeking escape through cathartic death. This study is casting a different gaze on female suicide bombing and finding out that religion is not the only reason why female suicide bombers detonate themselves. Death drive is not like the Buddhist belief of striving for annihilation for eternal peace. Through the analysis of selected novels, this research shed light to understand where this aberrant behaviour arises from and what its “drivers” are – externalised and projected through repression and senseless murderous rage. The study concludes that when hope diminishes, the female characters see martyrdom as the ultimate redemption, out of dire hopelessness and cruel condition they dwell in; there is the promise that they will have a better life in paradise. This research is relevant knowing that terrorism must be considered not as a personal problem, but a manifestation of the disintegration of the social order and therefore a dilemma for the integrated community to elucidate on.